A Method for Preliminary Estimation of the Length of Midship Body Block to Be Inserted During Ship’s Conversion - Michalski Jan P. (Polish Maritime Research, 2017)
The paper presents a method for preliminary estimation of the length of the midship body block, which inserted in the original hull, increases the deadweight of the ship in line with a required quantity. The method may be useful for establishing the scope of conversion to better adjust the ship for transportation tasks. The problem is formulated by using a mathematical model so selected that its solution, under set of assumptions, is obtained in a closed analytical form. The presented method can be useful for application to pre-investment analysis of the ship conversion costs and functional profits.